Acoustic monitoring data of anuran species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. Issue 5 (6th September 2020) - Yoshioka, Akira; Matsushima, Noe; Jingu, Shoma; Kumada, Nao; Yokota, Ryoko; Totsu, Kumiko; Fukasawa, Keita
Abstract: The Fukushima Daiichi power plant accident led to large‐scale and long‐term evacuation zones in which usual land‐use activities such as farming have been stopped. In particular, the loss of irrigated rice paddies is hypothesized to have seriously impacted freshwater biodiversity. In 2014, we started acoustic monitoring of frogs by using digital voice recorders in and around the evacuation zone. For the monitoring project, 52 and 57 monitoring sites were located within schoolyards (including those that had been converted into community centers) to examine the frog assemblages in the urban and rural landscapes of the region in 2014 and 2015, respectively. At each site, a digital voice recorder was installed during the period from May to July, and we recorded 10 min a day at night using a timed‐recording mode. We divided the audio data into 20‐s segments and identified species recorded in segments sampled from late May to late June (partly in early July). We identified eight frog species from 1, 962 audio segments in total (correspond to 4 days per year in principal). For each species, intensity of calling at four levels was also recorded as an index of abundance. We are continuing to monitor and intend to update the dataset with new observations hereafter. Our dataset will support scientists and experts in recognizing the status and dynamics of anuran assemblages in and around the evacuation zone and will contribute to the promotion of open science. The complete data set for this abstract published in the Data Paper section of the journal is available in electronic format in MetaCat in JaLTER at http://db.cger.nies.go.jp/JaLTER/metacat/metacat/ERDP-2020-12.1/jalter-en . Abstract : Acoustic frog monitoring inside and outside the Fukushima evacuation zone has been started since 2014. Now, the monitoring data are available online. Users can conduct analysis on their own (e.g., mapping frog species distribution around the evacuation zone, analyzing the effect of evacuation).